The Effectiveness of Guessing Game with Flip Chart Media in Teaching Vocabulary - Nurhayati, Nurhayati (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The aim of this study is to investigate the impact of a guessing game utilizing flip chart media on the vocabulary acquisition of seventh-grade students at SMPN 20 Kabupaten Sorong. The research design employed in this study was pre-experimental in nature. The study's population consisted of seventh-grade students from SMP Negeri 20 Kabupaten Sorong. The research sample consisted of 30 seventh-grade pupils. The researcher employed a set of 20 multiple choice items for both the pretest and posttest in order to gather data. The researcher utilized the SPSS application to compute the data during the analysis. The alternative hypothesis, which posited that the utilization of flip chart media in a guessing game had an impact on the vocabulary of students at SMP Negeri 20 Kabupaten Sorong, particularly those in class VII, was supported after conducting an analysis of the results obtained from the paired sample T test. Conversely, the null hypothesis was rejected. The obtained P-value (0.000) is more significant than the critical P-value (0.05). There was a substantial difference observed in the vocabulary scores of the pupils between the pretest and posttest. The utilization of flip chart media in the guessing game has a significant impact on the students' vocabulary.